ANALISIS KAUSALITAS GRANGER PERTUMBUHAN EKONOMI, UTANG LUAR NEGERI, KEMISKINAN, DAN PENGANGGURAN TERBUKA - martha situmorang (Pusat Kajian Anggaran, 2023)
This study analyzes the causality between Indonesia's economic growth, foreign debt, unemployment, and poverty rate. The data used is time series data for the research period 1984–2022. The analysis used in this study is a quantitative descriptive analysis method using the Granger analysis test. Based on the results of the Granger causality test, it can be concluded that there is a unidirectional Granger causality from the poverty rate to growth, there is no bidirectional Granger causality between foreign debt and growth, there is a unidirectional Granger causality from the open unemployment rate to the poverty rate, there is unidirectional Granger causality from the poverty rate to external debt, and there is a unidirectional Granger causality from the level of open unemployment to foreign debt.